Foundations of literacy : a balanced approach to language, listening and literacy skills in the early years - Palmer, S.; Bayley, R. (London : Featherstone, an imprint of Bloomsbury Publishing, 2013)
This fully revised fourth edition outlines seven strands of practice for three to six-year old children, designed to develop the skills, concepts and knowledge underpinning literacy in the early years. Accompanying each strand are clear explanations of the research and reasoning on which they are based. Practical advice on helping children transfer their learning into their own child-initiated activities, to build a genuine and solid foundation for literacy, is integral to the book